AI-Assisted Media in Language Learning: A SWOT Analysis from Lecturers’ and Students’ Perspective - Miftah Al Farhan; Istiqamah Istiqamah (GLENS: Global English Insights Journal, 2026)
This study explores the use of AI-assisted media in Indonesian and English language learning in Indonesian universities, focusing on media types, integration patterns, and lecturers’ and students’ perspectives on its SWOT aspects. The method used was explanatory qualitative research through in-depth interviews and focus group discussions with 6 lecturers and 6 students from five universities across Indonesia. The collected data were analyzed through developing themes, generating matrices, and establishing conclusions. The findings indicate that ChatGPT, Canva AI, and Gemini are the most frequently used AI media. The integration of AI tools occurs at nearly every stage of the learning process. It offers benefits such as improved access, information acquisition, and personalized learning, but it also presents drawbacks such as a reliance on technology that could potentially undermine social interaction and critical thinking. It brings opportunities for increased technological literacy and innovation, as well as threats like the digital divide, unclear regulations, plagiarism, and a decline in creativity. This study makes a theoretical contribution by developing a holistic framework for the integration of AI in learning that encompasses strengths, weaknesses, opportunities, and threats, and a methodological contribution through the systematic mapping of AI use across all stages of the learning process.